The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.3174/ajnr.a3887
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mastoid Pneumatization in Temporal Bone Fractures

Abstract: BACKGROUND AND PURPOSE:The mastoid portion of the temporal bone has multiple functional roles in the organism, including regulation of pressure in the middle ear and protection of the inner ear. We investigated whether mastoid pneumatization plays a role in the protection of vital structures in the temporal bone during direct lateral trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
0
26
1
Order By: Relevance
“…Nevertheless, the temporal bone pneumatization was measured in relation to previous studies [11], as well as the skin thickness at the impact area and bone mineralization. In fact, the mastoid pneumatization plays a role in the absorption and dispersion of kinetic energy during lateral temporal bone trauma [13].…”
Section: Perspectivesmentioning
confidence: 99%
“…Nevertheless, the temporal bone pneumatization was measured in relation to previous studies [11], as well as the skin thickness at the impact area and bone mineralization. In fact, the mastoid pneumatization plays a role in the absorption and dispersion of kinetic energy during lateral temporal bone trauma [13].…”
Section: Perspectivesmentioning
confidence: 99%
“…Finally, assessment of temporal bone pneumatization is important considering the role played by the mastoid portion of the temporal bone in the absorption and dispersion of kinetic energy during direct lateral trauma to the temporal bone [ 14 ].…”
Section: External and Middle Earmentioning
confidence: 99%
“…182 During anesthesia, MEP rises after nitrous oxide gas inhalation, and incidence of nausea and vomiting was higher in the small mastoid group versus the large mastoid group. 181 In another report based on nitrous oxide, Alper et al 183 found an inverse relationship between mastoid size and gas exchange rate, indicating that the mastoid was acting as an ME gas reserve.…”
Section: Physiology and Pathophysiologymentioning
confidence: 99%
“…Alicandri-Ciufelli et al 180 hypothesized that mastoid function is that of creating an adequate negative pressure for best performance in high-frequency or ultrasound sound transmission. Ilea et al 181 concluded that the MACS plays a role in the absorption and dispersion of kinetic energy during direct lateral trauma, reducing the incidence of fracture.…”
Section: Physiology and Pathophysiologymentioning
confidence: 99%